Continuous citrate-capped gold nanoparticle synthesis in a two-phase flow reactor - Damilos, Spyridon; Alissandratos, Ioannis; Panariello, Luca; Radhakrishnan, Anand N. P.; Cao, Enhong; Wu, Gaowei; Besenhard, Maximilian O.; Kulkarni, Amol A.; Makatsoris, Charalampos; Gavriilidis, Asterios (Journal of Flow Chemistry, 2021)
A continuous manufacturing platform was developed for the synthesis of aqueous colloidal 10-20 nm gold nanoparticles (Au NPs) in a flow reactor using chloroauric acid, sodium citrate and citric acid at 95 degrees C and 2.3 bar(a) pressure. The use of a twophase flow system - using heptane as the continuous phase - prevented fouling on the reactor walls, while improving the residence time distribution. Continuous syntheses for up to 2 h demonstrated its potential application for continuous manufacturing, while live quality control was established using online UV-Vis photospectrometry that monitored the particle size and process yield. The synthesis was stable and reproducible over time for gold precursor concentration above 0.23 mM (after mixing), resulting in average particle size between 12 and 15 nm. A hydrophobic membrane separator provided successful separation of the aqueous and organic phases and collection of colloidal Au NPs in flow. Process yield increased at higher inlet flow rates (from 70% to almost 100 %), due to lower residence time of the colloidal solution in the separator resulting in less fouling in the PTFE membrane. This study addresses the challenges for the translation of the synthesis from batch to flow and provides tools for the development of a continuous manufacturing platform for gold nanoparticles.
Keywords: Continuous manufacturing; Nanomaterials; Online analysis; phase separation; segmented flow